2010
DOI: 10.1177/0267659110378843
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased pump flow on hepatic blood flow and systemic inflammatory response following on-pump coronary artery bypass grafting

Abstract: Higher pump flows during hypothermic CPB increase hepatic blood flow. There was a trend towards attenuation of post-operative inflammatory response; however, larger studies will be needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, Adluri and his colleagues found that the reduced hepatic blood flow when commencing CPB can be balanced by an increase of the pump flow rate by 20%. [17] For their study they used the indocyanine green method which measured its percentage dye, and therefore overwhelmed the difficulty of the dual blood supply to the liver. In addition, reduction of blood flow through the splanchnic circulation cause to endotoxemia as it may end to the failure of the mucosal barrier in the GI tract.…”
Section: Blood Flow During Cpb: Goals and Requirementsmentioning
confidence: 99%
“…Furthermore, Adluri and his colleagues found that the reduced hepatic blood flow when commencing CPB can be balanced by an increase of the pump flow rate by 20%. [17] For their study they used the indocyanine green method which measured its percentage dye, and therefore overwhelmed the difficulty of the dual blood supply to the liver. In addition, reduction of blood flow through the splanchnic circulation cause to endotoxemia as it may end to the failure of the mucosal barrier in the GI tract.…”
Section: Blood Flow During Cpb: Goals and Requirementsmentioning
confidence: 99%